Effectiveness of Oral Probiotics as Adjuvant Therapy in Reproductive Aged Women with Vaginal Discharge - Indarti, Junita; Budidarmo, Utomo (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To investigate the efficacy of oral proboiotics and prove the high proportion of cure and satisfaction levels of post-treatment patients with a combination of antimicrobial-probiotic oral Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 compared to a combination of antimicrobial-placebo in the treatment of reproductive aged patients with vaginal discharge in the outpatient obstetrics and gynecologic clinic in Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia and Arifin Achmad Regional Hospital Pekanbaru, Riau, Indonesia. Methods:This was a randomized, double-blind, placebo-controlled trial involving50 subjects consisting of reproductive aged women. Data were collected using syndromic approach, probiotics were given as an adjuvant for standard antimicrobial therapy versus placebo as control, response was recorded 4 weeks later, for cure proportion and satisfaction level. Statistical analysis was performed to assess the variables. Interim analysis with conditional power assesment and futility testing were performed at midway due to insufficient sample size. Research was approved by Ethics Commitee for Health Researches Faculty of Medicine University of Indonesia-Dr. Cipto Mangunkusumo Hospital in March 2016. Results: A total of 50 subjects participated in this study. and analyzed (25 subjects in each group), cure proportion 56%(14) of the treatment and 60%(15)on the control group, with relative risk of 1.1, Chi-square test p value (0.77, 95% CI; 0.57 to 2 , 11). High satisfaction level (score ≥67) was higher in the placebo (52,6%, 10 subjects) compared to probiotic group (47,4%, 9 subjects), p value 0,65 (≥0,05). Conditional power and futility testing curve, revealed Z = -0.2865, conditional power 0.11 to 0.13, and futility index of 0.87 to 0.88, equals to low possibility of statistical significance with full sample size (84). Conclusion: There was no clinical and statistical difference in the proportion of cure rate and the level of satisfaction in patients of probiotics vs placebo groups after treatment for 4 weeks. The initial hypothesis of higher proportion of the cure ratein the treatment group still cannot be excluded, due to insufficient samples. Keywords: bacterial vaginosis, , lactobacillus reuteri RC-14, lactobacillus rhamnosus GR-1, randomized double blind controlled trial, trichomoniasis , vaginal discharge,  vulvovaginal candidiasis.